Self-assessment of some aspects of the quality of life residents under long-term care - Toczyńska, Aneta; Krajewska-Kułak, Elżbieta; Łukaszuk, Cecylia (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Introduction: Poland, is one of a number of countries in which the steadily growing demand for long-term care. Aim: To assess the self-selected aspects of quality of life in residents under the long-term care. Material and methods: The study was carried out among residents of the non-public Department of Caring and Treatment in Ustrzeszy. We used the following questionnaires and scales: ADL (Activities of Daily Living), Geriatric Depression Rating Scales (GDS) and the Acceptance of Illness Scale (AIS). Results: According to respondents nurse was a person who most often (37/56) and most (25/56) held the medical care of them. The news of illness caused fear in 27/56. Of the participants 40 respondents received medical diagnosis from a doctor. Most important for patients to ensure a sense of comfort was the participation of the family in care. Twenty-five percent of patients did not cope with the disease — they were passive and believed that the taking of any action does not make sense. The abovementioned was confirmed by AIS scale, where 30/56 of patients received less than 20 points. Most respondents afraid of failure and loneliness. The majority of residents evaluated their health and well being for three to five points at 10 score scale. The most troublesome for the patients were: movement difficulty (41/56), urinary incontinence (31/56) and fecal (27/56). Nearly 22/56 of the residents reported that disease caused a deterioration in their family relationships. Overall 43/56 of the participants achieved two or less points in ADL, indicating a significant disability. Almost 12 of patients have received 11 to 15 scores in the GDS scale, suggesting depression. Conclusions: The diagnosis of the disease in most patients resulted in anxiety and negative change in family relationships. The most important factor contributing to the comfort of a chronically ill was the family participation in patient care. The most troublesome in everyday life, inpatients reported the difficulties in movement, incontinence of urine and stool. Almost all patients reported diminished interest by disease activity.